Monitoring of cattle in confinement with the aid of drone, surveillance of welfare conditions and automated counting (Research, Society and Development, 2025)
The study aimed to evaluate the use of drones (UAS - Unmanned Aerial System) in monitoring confined cattle, with automated herd or individual cattle counting, focusing on disease detection and animal welfare monitoring. Flights were conducted using a DJI Mini 2 aerial device, operating at a minimum height of 5 meters over a cattle confinement area on a private property located in the municipality of Balsas, Maranhão. Observations were made for periods of 3 hours. The technology allowed for individual and group assessments of the animals, monitoring feeding areas, and checking for potential clinical signs of diseases. The unmanned aerial vehicle did not disturb the cattle, facilitating the detection of morbidity and mortality, while also reducing the need for labor. The Count Things from Photos app, integrated with the device, enabled the automated counting of cattle, emerging as an effective and low-cost technological innovation for sanitary surveillance and the welfare of confined cattle. The use of the unmanned aerial vehicle showed a high level of agreement with direct inspections and clinical examination of the animals and also demonstrated potential for monitoring cattle welfare from the confinement area to transport to the slaughterhouse, contributing to the traceability process of the animals. The app was effective in automated counting, whether individually or in groups of confined cattle.